The politics of poverty alleviation strategies in India - Vijayabaskar, M.,Balagopal, Gayathri (UNRISD, 2019)
In 2004, following the election of the Congress-led United Progressive Alliance (UPA), India began to introduce a series of legally enforceable rights to expand the economic security and social opportunities of its citizens. The flagship initiative of the UPA was the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA); a program which sought to protect the livelihoods of the poor agricultural labourers during periods of distress, by granting adult members of every rural household the right to demand 100 days of unskilled work at stipulated minimum wages from the state, making it the largest work guarantee programme in the world. The second measure was the National Food Security Act (NFSA), an improvement of the pre-existing public distribution system (PDS), through which state governments offered subsidised food grains to the poor. After establishing the historical antecedents of the MGNREGA and the PDS, this paper briefly reviews the politico-economic context of the emergence of these two initiatives in India. This includes the political and civil society imperatives that shaped the design and implementation of the schemes. Based on secondary data, the paper then examines the performance of the two programmes over time and across sub-national regions. The paper offers some explanations for the trends observed and sub-national variations. Explanations are based on both existing literature and interviews with key informants in the bureaucracy, political elites and civil society activists in New Delhi, Tamil Nadu and Rajasthan. Women, Dalits and Adivasis, who generally constitute the poorest inhabitants of rural India, have disproportionately benefitted from the MGNREGA, weakening traditional relations of power. The paper highlights, in conclusion, the need for a more local-sensitive approach to policy design and greater political mobilisation of intended beneficiaries for rights-based welfare programmes to be effective in addressing social and economic insecurities of the poor.
10419/246232
Keywords: Graue Literatur; Judicial activism; civil society activism; political mobilisation over social protection; MGNREGA; NFSA; PDS; state capacity